Template-free synthesis of nickel sulfides hollow spheres and their application in dye-sensitized solar cells. (July 2016) - Zuo, Xueqin; Yan, Shengnan; Yang, Bo; Li, Guang; Zhang, Haijun; Tang, Huaibao; Wu, Mingzai; Ma, Yongqing; Jin, Shaowei; Zhu, Kerong
Highlights: NiS and NiS2 hollow spheres were synthesized simultaneously. The phase transformed from NiS into NiS2 with the sulfur contents increasing. Both of them can substitute Pt as efficient CE catalyst of DSSCs. NiS2 CE exhibits superior electrocatalytic activity than NiS CE. Abstract: NiS and NiS2 hollow spheres were synthesized simultaneously by a facile solvothermal route without the help of any template or surfactant. The Ni/S molar ratio in the reactants plays a significant role in the formation of nickel sulfides with different stoichiometric ratio. The microstructures and morphologies of the NiS and NiS2 were investigated by X-ray diffraction, scanning electron microscopy, transmission electron microscopy and N2 adsorption–desorption isotherm measurements. In addition, the electrochemical performances of dye-sensitized solar cells based on these two types of nickel sulfides counter electrodes (CEs) were investigated in detail. It is found that NiS2 CE exhibit higher electrocatalytic activity than NiS CE for the reduction of triiodide. As a consequence, the DSSC with NiS2 CE generates higher power conversion efficiency (7.13%) than that with NiS CE (6.49%).